CTL AND BLENDED LEARNING MODELS IN IMPROVING LEARNING OUTCOMES - Ronald, Jimi; Amelia, Mona; Eprillison, Vivina; Stevani, Stevani; Amaluis, Dina; Pratama, Indra Mulia; Selvia, Nisha (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2023)
Contextual Teaching And Learning (CTL) and Blended Learning models are learning models that both improve student learning outcomes. The purpose of this study was to analyze the effect of the Contextual Teaching And Learning (CTL) Learning Model on the learning outcomes of students in Class 2022 A of the Economic Education Study Program, Faculty of Economics and Business, Universitas PGRI Sumatera Barat, to analyze the effect of the Blended Learning Model on the learning outcomes of students in Class 2022 B of the Economic Education Study Program, Faculty of Economics and Business, Universitas PGRI Sumatera Barat, and to see the difference in the effect of the Contextual Teaching And Learning (CTL) Learning Model with the Blended Learning Model on the learning outcomes of students in Class 2022 of the Economic Education Study Program, Faculty of Economics and Business, Universitas PGRI Sumatera Barat. The method in this study uses the Quasy Experiment method, with the population being 108 batch students with the sample being batch 2022 A and 2022 B with a total of 50 people. The hypothesis test used is using factorial analysis which is modified by a different test. From the results of the study obtained the results that: there is an effect of the Contextual Teaching And Learning Model (CTL) on the learning outcomes of students in Class 2022 A of the Economic Education Study Program, Faculty of Economics and Business, Universitas PGRI West Sumatra, there is an effect of the Blended Learning Model on the learning outcomes of students in Class 2022 B of the Economic Education Study Program, Faculty of Economics and Business, Universitas PGRI West Sumatra, and there is a difference in the effect of the Contextual Teaching And Learning Model (CTL) with the Blended Learning Model on the learning outcomes of students in Class 2022 of the Economic Education Study Program, Faculty of Economics and Business, Universitas PGRI Sumatera Barat.